2021
DOI: 10.15857/ksep.2021.30.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 8 Weeks Un-tact Pilates Home Training on Body Composition, Abdominal Obesity, Pelvic Tilt and Strength, Back Pain in Overweight Women after Childbirth

Abstract: Purpose: This study aims to observe the effects of at home Pilates exercise, using a real-time web program in postpartum women where measurements of body composition, abdominal obesity, pelvic tilt, back pain and Oswestry Disability Index will be taken.Methods: Subjects included postpartum women under the age of 45 that were registered at the C Cultural Women’s Center in Bundang, Gyeonggi-do. All subjects were within 1 year of childbirth, had no medical opinion and were not receiving medication. A total of 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Pehlivan et al [ 2 ] reported that the telerehabilitation exercise program for COVID-19 patients had a significant effect on improving respiratory function, quality of life, and physical function, and that it is an exercise program that can be applied in real life only when it is carried out without special equipment. Hyun and Cho [ 4 ] reported that non-face-to-face home Pilates exercise had a significant effect on relieving pain and improving physical strength for postpartum women. They showed a significant effect on neck pain relief and physical function improvement when telerehabilitation exercise programs were applied to RSP subjects, which is consistent with the mediating effect of existing face-to-face neural mobility [ 26 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pehlivan et al [ 2 ] reported that the telerehabilitation exercise program for COVID-19 patients had a significant effect on improving respiratory function, quality of life, and physical function, and that it is an exercise program that can be applied in real life only when it is carried out without special equipment. Hyun and Cho [ 4 ] reported that non-face-to-face home Pilates exercise had a significant effect on relieving pain and improving physical strength for postpartum women. They showed a significant effect on neck pain relief and physical function improvement when telerehabilitation exercise programs were applied to RSP subjects, which is consistent with the mediating effect of existing face-to-face neural mobility [ 26 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies on telerehabilitation, active participation in appropriate telerehabilitation exercise program reportedly facilitated obesity prevention and provided back pain relief in women after childbirth [ 4 ], and improved the range of motion and balance in knee arthritis patients [ 5 ]. In addition, when telerehabilitation was applied to people with COVID-19 and post-COVID-19 conditions, the effect of improving physical function and reducing dyspnea was confirmed [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regular Pilates exercise reduces the levels of triglycerides (TG), low-density lipoprotein (LDL) cholesterol, and insulin resistance, thereby preventing gestational diabetes; it also reduces the fear of childbirth, anxiety, fatigue, and stress during pregnancy [18] . Postpartum women's participation in Pilates also reduces the levels of visual analog scale (VAS) and Oswestry Disability Index (ODI), which are back pain indices, and have a signi cant effect on weight, waist circumference, and WHR reduction after childbirth [19,20] . However, after COVID-19, it has become di cult for women to exercise, and there is a signi cant lack of alternative methods for prenatal management.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in nutritional intake and dietary behavior under the COVID-19 pandemic have made people gain weight (8,9), which is believed to greatly affect daily life by causing mental and physical problems (10). In other words, the COVID-19 pandemic has created an environment that makes prone to obesity by causing problems, such as a decrease in physical activity, irregular eating, and depression (11).…”
Section: Introductionmentioning
confidence: 99%